Study on implementation of MSPO among oil palm smallholder / Muhammad Lutfi Mohd Kamal - Mohd Kamal, Muhammad Lutfi (2018)
Malaysia Palm Oil Board (MPOB) formally announced Malaysian Sustainable Palm Oil in 2013. MSPO was introduced because of some black campaigns that were made by other commodity competitor to defame the palm oil-based commodity. The MSPO standard was designed to provide good accountable management to achieve positive social, economic, and environmental effects, in addition to minimizing adverse effects, especially on human and the environment. However, smallholders have a difficulty to manage the oil palm properly due to some factors such as lack of awareness on environmental issue and financial resources. The survey was made to determine the perspective of oil palm smallholders toward the implementation of MSPO standard, Theory of Planned Behavior was applied as conceptual framework for conducting the survey. The survey was conducted in Felda Keratong 5 at Muadzam Shah, Pahang due to current situation of smallholder here. Based on Raosoft calculator sampling, out of 136 of total population, the targeted respondent is 101 people. Factor analysis and correlation analysis was used to analyze the gathered information. Based on factor analysis, four factors were identified namely attitude, subjective norms, perceived behavioral control, and knowledge. Subjective norms were identified as a factor influence MSPO implementation toward smallholders. Based on correlation analysis, attitude and knowledge have a moderate relationship towards the intention of MSPO implementation among oil palm smallholders. In conclusion, oil palm smallholders believes that MSPO practice will increase their income, improve their social life and make them sustainable in oil palm industry.